Synergistic effect of microbe-associated molecules on human monocyte-derived dendritic cell maturation in vitro - Skivka, L.M.; Shvets, Yu.V.; Khranovska, N.M.; Fedorchuk, O.G.; Pozur, V.V; Senchilo, N.V. (Вiopolymers and Cell, 2012)
Microbe-associated molecules (MAM) are known to exert stimulating effect on the dendritic cell (DC) maturation. The aim of this investigation was a comparative study of the effect of different MAMs, used separately and in combination, on human monocyte-derived DC maturation in vitro. Methods. The studied MAMs were represented by lipopolysaccharide (LPS) from Escherichia coli and different biopolymers from Staphylococcus aureus Wood 46. DC phenotype was analyzed by flow cytometry. Functional maturity of DC was assessed in the mixed leukocyte reaction. Results. The use of MAMs in combination has been shown to be more efficient for phenotypic and functional maturation of monocyte-derived DCs than utilizing different MAMs separately. The most potent stimulatory effect has been observed for the combination of LPS with peptidoglycan (PepG) or teichoic acid with PepG. Conclusions. Combined use of different MAMs, especially those that activate different signaling pathways (LPS-PepG and teichoic acid-PepG), results in synergistic stimulation of monocyte-derived DC maturation.